2013
DOI: 10.1097/lbr.0b013e31829bccba
|View full text |Cite
|
Sign up to set email alerts
|

Endobronchial Inflammatory Pseudotumor

Abstract: Inflammatory pseudotumors of the lung are a group of non-neoplastic tumors, which are mainly of parenchymal origin and rarely endobronchial. We report a case of a 9-year-old girl who presented with left-sided tension pneumothorax and subcutaneous emphysema. After emergency management, chest computed tomography revealed an ill-defined left lung mass. Rigid bronchoscopy revealed a mass occluding the left main bronchus at the origin of the left upper lobe bronchus. Initially, the mass was thought to be a foreign … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…Although recurrence is described as a rare phenomenon (14% of pulmonary IMT) a close follow-up should be made for the early recognition of tumor relapse. In addition, the local invasion at diagnosis was highly correlated with local relapse ( 9 , 11 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although recurrence is described as a rare phenomenon (14% of pulmonary IMT) a close follow-up should be made for the early recognition of tumor relapse. In addition, the local invasion at diagnosis was highly correlated with local relapse ( 9 , 11 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…All the patients have a histological diagnosis of IMT, but ALK status was reported in only five cases. Treatment strategy are listed in Supplemental Table 1 [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] . Aggressive surgery was the primary approach considering the critical condition in more than 50% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Bronchoscopy and transbronchoscopic biopsy are necessary for the evaluation, diagnosis and treatment of airway obstructive injury (25)(26). Studies have found that the diagnosis of IMT is mainly determined by histopathology and immunohistochemical examination through biopsy (13)(14)(15)(16)(17)(18)(19)(20)(21). The pathological manifestations of IMT are as follows: [1] A large number of proliferating spindle cells are arranged in bundles; [2] The nuclei may be slightly heteromorphic, with mitotic images occasionally seen; [3] Lack of pathological mitosis and coagulation necrosis; [4] A mixture of spindle cells, lymphocytes, plasma cells and eosinophils existed (2,27).…”
Section: Discussionmentioning
confidence: 99%